2009
DOI: 10.1016/j.neuroimage.2009.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of age on long white matter tracts using diffusion tensor tractography

Abstract: Aging is associated with significant white matter deterioration and this deterioration is assumed to be at least partly a consequence of myelin degeneration. The present study investigated specific predictions of the myelodegeneration hypothesis using diffusion tensor tractography. This technique has several advantages over other methods of assessing white matter architecture, including the possibility of isolating individual white matter tracts and measuring effects along the whole extent of each tract. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

89
354
6
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(461 citation statements)
references
References 95 publications
89
354
6
3
Order By: Relevance
“…1b). Note that the FA values in the genu of CC for both groups (bilinguals: M ϭ 0.47, SD ϭ 0.04; monolinguals: M ϭ 0.44, SD ϭ 0.03) were lower than those usually reported for younger adults (M ϭ 0.55, SD ϭ 0.04 from Davis et al, 2009), as would be expected.…”
Section: Resultssupporting
confidence: 58%
“…1b). Note that the FA values in the genu of CC for both groups (bilinguals: M ϭ 0.47, SD ϭ 0.04; monolinguals: M ϭ 0.44, SD ϭ 0.03) were lower than those usually reported for younger adults (M ϭ 0.55, SD ϭ 0.04 from Davis et al, 2009), as would be expected.…”
Section: Resultssupporting
confidence: 58%
“…Some studies 49,55 have found that age differences in activation within PFC were mediated by white matter integrity, such that more intact white matter was related to more activation, but others have failed to find this effect 94,136 . Despite this inconsistency in results, the use of DTI to assess white matter integrity holds considerable promise for the study of cognitive aging, particularly as the integrity of specific tracts has been shown to be related to speed of performance in older adults 137 or to accuracy of performance [138][139][140] . Of particular interest will be studies examining the relations among white matter integrity underlying specific functional networks, functional connectivity in those networks, and how these measures are related to behaviour in older adults.…”
Section: Brain Structurementioning
confidence: 99%
“…But, in a study with a larger subject pool, FA declined with age in the frontal, parietal, and temporal cortices and correlated with deficits in executive function (Grieve et al 2007). WM deficits were also found to occur to a greater extent in the anterior segments of fiber tracts in the frontal and parietal cortices and increased RD in the anterior tracts corresponded with worse executive performance (Davis et al 2009). Impairments in working memory, problem solving, and motor function were also correlated with an agerelated decrease of FA in anterior and superior fiber tracts, which was interpreted to reflect myelin damage and fluid accumulation in regions around the axon (Zahr et al 2009).…”
Section: Diffusion Tensor Imaging In Humansmentioning
confidence: 99%